Identifying barriers to implementation of local transport policy – Lessons learned from case studies on bus policy implementation in Great Britain. (June 2020) - McTigue, Clare; Rye, Tom; Monios, Jason
Abstract: Previous work by the authors has addressed the issue of local bus policy implementation in Britain outside London by studies of local transport documents, survey and interviews of local transport officers working in local authorities. The findings from these studies highlight that some of the key elements to successful implementation could be understood in more depth by taking a case study approach. This paper analyses four case studies of the implementation of specific bus policy measures in four different cities in Great Britain: the Quality Contract Scheme (QCS) in Tyne and Wear, the Fastlink Scheme in Glasgow, a Bus Priority Scheme in Solihull and a Smart Ticketing Scheme in Dundee. The findings in this paper show that policy champions, collaboration and interaction help to build a relationship between the parties involved, ensure limited changes due to bureaucratic power and changes to the policy, and help to overcome opposition, conflict and ambiguities. It is important that those involved in the policy process are provided with relevant training, supervision and support to help overcome the staffing difficulties and to deal with barriers external to the implementing organisation such as economic, social and political conditions. Highlights: Greatest influences on implementation are identified. Greatest challenges faced by local authorities are identified. Those involved in policy process require relevant training, supervision and support. Authorities must be certain from the planning stage that resources are available. Clear strategies and tactics improve policy development and collaboration, stakeholder engagement and decision making.